A year in the life of a Shinto shrine - Nelson, John K. (John Kenneth), 1953- (ACLS Humanities E-Book., 1996)
What we today call Shinto has been at the heart of Japanese culture for almost as long as there has been political entity distinguishing itself as Japan. A Year in the Life of a Shinto Shrine describes the ritual cycle at Suwa Shrine, Nagasaki's major Shinto shrine. Conversations with priests, other shrine personnel, and people attending shrine functions supplement John K. Nelson's observations of over fifty shrine rituals and festivals. He elicits their views on the meaning and personal relevance of the religious events and the place of Shinto and Suwa Shrine in Japanese society, culture, and politics. Nelson focuses on the very human side of an ancient institution and provides a detailed look at beliefs and practices that, although grounded in natural cycles, are nonetheless meaningful in late-twentieth-century Japanese society.